The Challenges of History Education in Iceland. (1st May 2013) - Margrét Gestsdóttir, Súsanna
In this article the author discusses the teaching of history in Iceland, first and foremost in relation to the environment in which the subject finds itself, the legislation relating to it and the curriculum. Curriculum development over the past decades is examined, in addition to changes in teaching material and the general attitudes that have influenced both of these from the time of the struggle for national independence in the former half of the twentieth century. There is a discussion of the disputes that have arisen as a result of tampering with the curriculum and teaching material in history in recent years, both when new emphases were introduced in the eighties and when history teaching in upper secondary schools was substantially reduced with the new curriculum in 1999. Considerable attention is given to history teaching in upper secondary schools, despite there being a dearth of research at this level. There is quite a degree of evidence that history is popular amongst Icelandic students and the public at large. In this article, an attempt is made to analyse the state of history as a school subject in Iceland, not least in the light of the extensive freedom enjoyed by teachers in their jobs, bearing in mind that there are no standardized exams in the subject and no supervision of teaching methods. At present there is a review of the curricula at all school levels in Iceland and the future of history as a subject is therefore rather uncertain.